The Quality of Financial Reporting in the Digital Era: The Influence of ERP Transformation and Accounting Information Systems - Samsidar Samsidar (Dhana, 2026)
The rapid development of digital technology has significantly transformed financial reporting practices in modern organizations. The adoption of Enterprise Resource Planning (ERP) systems and Accounting Information Systems (AIS) has become increasingly important in improving the efficiency, accuracy, and transparency of financial reporting processes. However, the effectiveness of these technologies in enhancing financial reporting quality remains a critical issue, particularly in the context of digital transformation within organizations. Therefore, this study aims to analyze the influence of ERP transformation and accounting information systems on the quality of financial reporting in the digital era. This study employs a quantitative research approach using survey data collected from accounting staff, financial managers, and information system administrators involved in financial reporting processes. Data were obtained through structured questionnaires distributed to respondents working in organizations that have implemented digital accounting systems. The collected data were analyzed using multiple regression analysis to examine the relationship between ERP transformation, accounting information systems, and financial reporting quality. The results indicate that ERP transformation and accounting information systems have a positive and significant effect on financial reporting quality. ERP systems improve data integration, automate accounting processes, and enable real-time reporting, thereby enhancing the relevance and timeliness of financial information. Meanwhile, effective accounting information systems strengthen transparency, reliability, and data security in financial reporting. In conclusion, the integration of ERP transformation and accounting information systems plays a crucial role in improving financial reporting quality and supporting greater transparency and accountability in the digital era.